A Quantitative Analysis on the Satisfaction of Residents on the Integration and Development of the Chengdu-Chongqing Economic Circle - Chen, Shi; Trinidad, Maria Elizabeth (Indonesian Journal of Economics and Management, 2024)
The developments regarding circular economy during the past decades introduced the economic model called â€œEconomic Circleâ€ or â€œCircular Economyâ€. This model seeks to change the direction of the economic landscape from an expendable system to a more sustainable and regenerative one. In this study, a rising economic circle around the cities of Chengdu and Chongqing were examined. Particularly, this study aimed to answer, â€œWhat is the satisfaction level of Chengdu and Chongqing residents along economic, societal, technological and innovation, and environmental factors that influence the integration and development of the Chengdu-Chongqing economic circle?â€. Descriptive research design was used to identify the aforementioned factors and a 58-item questionnaire was distributed to a total of 210 respondents along these areas. It was found in the study that the residents are generally satisfied with the progress and initiatives related to these factors. While residents are satisfied overall, it is important to maintain a balanced approach to development. This means ensuring that economic growth is accompanied by measures that promote societal well-being, technological advancements, and environmental sustainability.